The cGas–Sting Signaling Pathway Is Required for the Innate Immune Response Against Ectromelia Virus - Cheng, Wen-Yu; He, Xiao-Bing; Jia, Huai-Jie; Chen, Guo-Hua; Jin, Qi-Wang; Long, Zhao-Lin; Jing, Zhi-Zhong (Frontiers in Immunology, 2018)
Activation of the DNA-dependent innate immune pathway plays a pivotal role in the host defense against poxvirus. Cyclic GMP-AMP synthase (cGAS) is a key cytosolic DNA sensor that produces the cyclic dinucleotide cGMP-AMP (cGAMP) upon activation, which triggers stimulator of interferon genes (STING), leading to type I IFN production and an antiviral response. Ectromelia virus (ECTV) has emerged as a valuable model for investigating the host-orthopoxvirus relationship. However, the role of cGas-Sting pathway in response to ECTV is not clearly understood. Here, we showed that murine cells (L929 and RAW264.7) mount type I IFN responses to ECTV that are dependent upon cGas, Sting, TANK binding kinase 1 (Tbk1), and interferon regulatory factor 3 (Irf3) signaling. Disruption of cGAS or STING expression in mouse macrophages blocked the induction of type I IFN production and facilitated ECTV replication. Consistently, mice deficient in cGas or Sting exhibited lower type I IFN levels and higher viral loads, and are more susceptible to mousepox caused by an infection with ECTV. Collectively, our study indicates that the cGas-Sting pathway is critical for the detection of ECTV infection, the induction of type I IFN production, and controlling ECTV replication.